REVIVING TRADITIONAL JAMU: THE CREATION OF HERBALIS MILK IN KELURAHAN KARYA JAYA, TEBING TINGGI - Isfenti Sadalia; Beby Kendida Hasibuan; Marina Wulandari Nasution; Dona Tiara Lubis; Lailan Syafrina Hasibuan; Isdiana Syahfitri (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
Kelurahan Karya Jaya is a community where a significant number of people engage in jamu production. The community service program Revitalizing Traditional Jamu: The Development of Herbalis Milk in Kelurahan Karya Jaya, Tebing Tinggi aims to strengthen the potential of traditional jamu by innovating their presentation into herbal-based milk products. Jamu, one of Indonesia’s cultural heritage, is frequently viewed as unappealing to younger generations because of its bitter flavor and traditional presentation. Transforming jamu into herbal milk not only enhances its taste but also boosts its nutritional benefits and makes it more acceptable to consumers, particularly children and young people. The problems identified include limited knowledge of residents in product diversification, lack of skills in hygienic and modern processing, and minimal access to packaging technology that is attractive and marketable. To resolve these challenges, we provide training and workshops on turning jamu into herbalis milk, practical guidance and direct teaching during the production process, as well as assistance in packaging and marketing strategies. This activity is expected to revitalize the traditional jamu culture, create added economic value for the community, and open wider market opportunities through innovative herbal milk products. The methods used in this service activity are training and practice, mentoring, and monitoring and evaluation.